Cross-sectional study on exercise capacity in obese patients with severe obstructive sleep apnea syndrome - Mei, Shengrui; Zhou, Yue; Wu, Wenjun; Cui, Xiaochuan; Cai, Junyan; Yuan, Peng; Deng, Shukun (Frontiers in Physiology, 2025)
ObjectiveTo explore the exercise capacity in obese patients with severe obstructive sleep apnea syndrome (OSAS) through cardiopulmonary exercise test (CPET).MethodsIn this cross-sectional study, patients with simple obesity (36 cases) and obese patients with severe OSAS (45 cases) admitted to the Department of Rehabilitation Medicine and the Department of General Practice of the Affiliated Wuxi People’s Hospital of Nanjing Medical University from September 2019 to January 2024 were collected. Additionally, we included 33 patients (BMI<28 kg/m2,AHI<5/hour) as a control group. All participants underwent CPET and polysomnography monitoring. The differences of polysomnography and CPET among the three groups were compared. To evaluate the correlation between AHI and the observed indexes.ResultsNo significant differences were observed in the proportion of men and women, age, height, exercise habit among the three groups (P > 0.05). Sleep monitoring data indicated that there were statistically significant differences among the three groups of patients in terms of the AHI, sleep efficiency, min SaO2, mean SaO2, and TS < 90%. In terms of the cardiopulmonary exercise test indexes, there were no statistically significant differences among the three groups of patients in VO2AT, while there were statistically significant differences in VO2AT%Pred and VO2AT/kg. Similar results were observed for maximum oxygen consumption, with no statistically significant differences in VO2peak among the three groups, but statistically significant differences in VO2peak%Pred and VO2peak/kg. There were statistically significant differences among the three groups of patients in HRmax,HRmax%Pred, HRr, VO2/HRmax, and VO2/HRmax %Pred. The correlation analysis indicated that AHI was positively correlated with TS < 90%,VO2/HRmax, BMI and negatively correlated with sleep efficiency, minSO2, mean SO2,VO2AT%Pred, VO2AT/kg, VO2peak%Pred, VO2peak/kg, HRmax, HRmax%Pred,HRr, VO2/HRmax%Pred, WRmax%Pred, and VEmax%Pred. Univariate and multivariate linear regression analyses showed that AHI was significantly negatively associated with multiple indicators of the cardiopulmonary exercise test (CPET). In the univariate model, for every 1-unit increase in AHI, all CPET indicators decreased significantly (p < 0.01). After adjusting for confounding factors such as gender, age, exercise habits, smoking history, hypertension and diabetes, the multivariate model still maintained significant correlations.ConclusionSevere OSAS, as a severe complication of obesity, further exacerbates the decline in exercise capacity among obese patients, with the extent of impairment positively correlated with AHI values.CPET can be used to assess cardiopulmonary function in patients with obesity and OSAS. Early intervention can be carried out for obese patients with severe OSAS who show a downward trend in cardiopulmonary exercise indicators.